Galectin-9 regulates HTR8/SVneo function via JNK signaling. Issue 1 (January 2021) - Li, Mengdie; Peng, Xiandong; Qian, Jinfeng; Sun, Fengrun; Chen, Chunqin; Wang, Songcun; Zhang, Jianping; Du, Meirong
Abstract : To obtain a successful pregnancy, trophoblasts must provide a physical barrier, suppress maternal reactivity, produce immunosuppressive hormones locally, and enhance the production of blocking factors that are able to bind to several antigenic sites. Inadequate placental perfusion has been closely associated with several pregnancy-associated diseases. Galectin-9 (Gal-9) has a wide variety of regulatory functions in innate and adaptive immunity during infection, tumor growth, and organ transplantation. We utilized immortalized human first-trimester extravillous trophoblast cells (HTR8/SVneo) for our functional study and examined the effects of Gal-9 on apoptosis, cytokine production and angiogenesis of HTR8/SVneo cells. Gal-9 inhibited the apoptosis and IFN-γ and IL-17A production, promoted IL-4 production, and coordinated the crosstalk between HTR8/SVneo cells and human umbilical vein endothelial cells via its interaction with Tim-3. Blockade of JNK signaling inhibited Gal-9 activities in HTR8/SVneo cells. In addition, we detected a correlation between low levels of Gal-9 and spontaneous abortion. So Gal-9 could inhibit the apoptosis and proinflammatory cytokine expression, and promote the angiogenesis and IL-4 production in HTR8/SVneo cells via Tim-3 in a JNK dependent manner to help the maintenance of normal pregnancy. These findings possibly identify Gal-9 as a key regulator of trophoblast cells and suggest its potential as a biomarker and target for the treatment of recurrent pregnancy loss.